Core Homologous Recombination Mutations and Improved Survival in Nonpancreatic GI Cancers. (4th April 2022) - Tan, Elaine; Whiting, Junmin; Knepper, Todd; Xie, Hao; Imanirad, Iman; Carballido, Estrella; Felder, Seth; Frakes, Jessica; Mo, Qianxing; Permuth, Jennifer B.; Somerer, Katelyn; Kim, Richard; et al.
Abstract : Introduction: Homologous recombination mutations (HRM) have led to increased responses to platinum chemotherapy in pancreatic cancer. However, HRMs' role in nonpancreatic gastrointestinal (GI) cancers remains to be determined. Our objective was to evaluate the prognostic and predictive role of core ( BRCA1, BRCA2, PALB2 ) and noncore HRM in nonpancreatic GI cancers receiving platinum therapy. Materials and Methods: This study performed at Moffitt Cancer Center included metastatic nonpancreatic GI cancer patients treated with platinum therapy. All patients had either a core or noncore HRM, determined by next generation sequencing. Response rates, median progression-free survival (PFS), and median overall survival (OS) were determined and compared between core versus noncore HRM patients. Results: In the study, 69 patients with one or more HRM were included: 63.8% were male, 87.0% were Caucasian, and 47.9% had colorectal cancer. Twenty-one (30.4%) patients had a core HRM and 48 (69.6%) had a noncore HRM. Among evaluable patients (n=64), there was no significant difference in objective response: 20.0% with core HRM versus 22.7% with noncore HRM responded to platinum therapy ( P =0.53). Median PFS was 10.4 months versus 7.1 months for core HRM versus noncore HRM, respectively ( P =0.039). Median OS was 68.9 months versus 24.3 months ( P =0.026) for core HRM versus noncore HRM, respectively. Conclusions: Our study demonstrated response of core and noncore HRM to platinum therapy in metastatic nonpancreatic GI malignancies, suggesting benefit in both groups. Core HRM patients had significantly increased median OS and median PFS compared with those with noncore HRM, suggesting potential prognostic and predictive significance. Larger prospective studies are needed to confirm our findings.